AUTHENTIC LEADERSHIP BEHAVIOR IN MADRASAH ALIYAH IN TASIKMALAYA REGENCY AAN KOMARIAH - Aan Komariah (The Faculty of Tarbiyah and Teacher Training associated with PSPII, 2015)
This research aims to know the relation between Spiritual Intelligence and Leader Personality with Authentic Leadership Behaviour. This research uses quantitative research approach with type of correlation approach. This research is done at 77 headmasters of Mardasah Aliyah in Tasikmalaya Regency. The samples are done by using simple random sampling technique. The research result shows that there is positive between Spiritual Intelligence and Leader Personality with Authentic Leadership Behaviour. The positive correlation coefficient shows that if the Spiritual Intelligence increases, so the authentic leadership behaviour will also increase. Also with the increasing of Leader Personality will increase the Authentic Leadership behaviour. The Spiritual Intelligence and Leader Personality all together affect significantly to the Authentic Leadership Behaviour.